Преваленција, искључивање вредности и варијантни спектар Г6ПД Дефициен-ЦИ пацијенти: на основу популације-кохорта 31482. Неонати ФР-ом новорођенче Сцреенинг међу Хефеи, Фуианг и Анкинг Цитијем - Li, Hui; Ch’ih, Yah; Li, Meiling; Luo, Yulei; Liu, Hao; Xu, Junyang; Song, Wangsheng; Ma, Qingqing; Shao, Ziyu (Journal of Medical Biochemistry, 2023)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is an X-linked recessive Mendelian genetic disorder,characterized by neonatal jaundice and hemolytic anemia,affecting more than 400 million people worldwide. The purpose of this research was to investigate revalence rates of G6PD deficiency and to evaluate establish specific cut-off values in early prediction of G6PD deficiency by regions(Hefei,Fuyang,Anqing) on different seasons ,as well as to investigate the frequencies of G6PD gene mutations among three regions mentioned above.Methods: A total of 31482 neonates (21402, 7680, and 2340 for Hefei, Fuyang, and Anqing city, respectively) were recruited. G6PD activity conducted on Genetic screening processor (GSP analyzer,2021-0010),was measured following manufacturer’s protocol.The cut-off value was firstly set to 35U/dl Hb.Positive subjects were recalled to attend genetic test for diagnosis.The receiver operating characteristics (ROC) curve was employed to assess and compare the efficienc-y of G6PD deficiency in the prediction of G6PD deficiency among Hefei,Fuya-ng and Anqing city on different seasons. Data was analyzed using SPSS (v. 25.0, IBM, Chicago, IL, USA)and MedCalc (v. 19.05, Ostend, Belgium). Mappin-g was performed using GraphPad Prism 9.00 (GraphPad Software, La Jolla, C-A, USA)Results: A total of 31482 participants were screened for G6PD deficiency,and 29 neonates were finally identified with G6PD deficiency,having a overall reval-ence rates of 0.09%.Results the incidence rate on the G6PD deficiency was 0.10% (22/21380)for Hefei city, 0.04%(3/7667) for Fuyang city, and 0.17%(4/239-6) for Anqing city.The optimal cut-off values of ROC curve in the prediction of G6PD deficiency was 26.55 U/dl Hb for Hefei city(Spring:21.80 U/dl Hb,Su-mmer:26.55 U/dl Hb, Winter: 23.16 U/dl Hb),for 6.35 U/dl Hb Fuyang city ,7-.15 U/dl Hb for Anqing city. R463H (17/57,29.82%)was the most frequent variation,followed with R459L(15/57,26.31%),H32R(8/57,14.04%),L342F(6/57,10.53%),V291M (6/57,10.53%). Conclusion: We have established the optimal cut-off values of G6PD activity in prediction of G6PD deficiency among Hefei,Fuyang and Anqing city on different seasons ,which will aid early detection of G6PD deficiency among neonates of regions mentioned above.We have also investigated the prevalence of the regions and discovered the frequency mutations.Those results will help G6PD screening promotion and precision diagnosis for Anhui province.